Preparation method and application of nanoparticle cross-linked temperature-resistant slow-swelling particles
Through emulsion polymerization and crosslinking reaction technology, temperature-resistant and slow-expansion particles were prepared, which solved the shortcomings of existing bulk expansion particles in temperature resistance, expansion rate and elasticity, and realized the preparation of high-performance nanoparticle crosslinked temperature-resistant slow-expansion particles, which was suitable for applications in reservoir depth development.
Patent Information
- Application Number
- CN202411976807.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The existing bulk expansion particles have shortcomings in temperature resistance, expansion rate and elasticity, which affects their application in reservoir depth development.
Core-shell nanoparticles were prepared by emulsion polymerization technology, and cross-linking reactions were carried out on the basis of them to form temperature-resistant and slow-swelling particles. The method includes emulsion polymerization using acrylate, styrene, surfactant and initiator, followed by addition of a polymerizable silane compound and initiator for further reaction, and finally adding an acrylamide compound, an amino group-containing silane compound and bentonite for crosslinking reaction.
The prepared nanoparticle cross-linked temperature-resistant and slow-expansion particles have good temperature resistance (can be temperature resistant to 150℃), slow-expansion properties and elasticity. They are suitable for materials that improve recovery rates and have a wide range of market application prospects.
Smart Images

Figure CN119735759A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil extraction, in particular to a preparation method and application of nanometer particle cross-linked temperature-resistant slow-swelling particles. Background Art
[0002] Volume-swelling particles have been widely used to plug large pores in oil reservoirs. Many types of volume-swelling particles have also been developed, such as polyacrylamide particles, polymers of bentonite and acrylamide, polymers of rubber and acrylamide, etc. Although these volume-swelling particles show good performance, their shortcomings are also obvious. They have poor temperature resistance, fast expansion rate, insufficient elasticity and other disadvantages, which seriously affect the application of volume-swelling particles. With the deep development of oil reservoirs, the demand for volume-swelling particles is increasing. High-performance volume-swelling particles suitable for complex reservoir conditions are urgently needed in the market.
[0003] Nanoparticles, as a type of material with excellent performance, have been applied in many fields. As dopants and crosslinkers, they can significantly improve the performance of materials. Polyacrylate particles have been widely used in industries such as coatings, inks, and adhesives. Polyacrylate nanoparticles are used as crosslinkers to copolymerize with acrylamide compounds and bentonite to form a polymer with a spatial network structure. The water absorption of polyacrylamide compounds, the hydrophobicity of polyacrylates, and the temperature resistance of bentonite are used. Under the action of the crosslinked network structure of polyacrylate nanoparticles, the material is endowed with heat-resistant and slow-swelling properties. The preparation of nanoparticle crosslinked heat-resistant and slow-swelling particles is very important for improving oil recovery. Therefore, it is urgent to design a preparation method for nanoparticle crosslinked heat-resistant and slow-swelling particles. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing nano-particle cross-linked temperature-resistant slow-swelling particles and their application, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles, the preparation method comprises the following steps: step 1: preparation of core-shell nanoparticles;
[0007] Take 0.2-0.4 parts by weight of a surfactant, 5-10 parts by weight of an acrylate, 1-2 parts by weight of styrene and 50 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 1; take 0.5-1 parts by weight of a polymerizable silane compound and 5 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 2; take 0.1-0.2 parts by weight of an initiator and 10 parts by weight of deionized water, mix and dissolve them to obtain an initiator solution; take 0.1-0.2 parts by weight of sodium bicarbonate and 30 parts by weight of deionized water, put them in a three-necked flask, stir and dissolve them, then heat them to 85° C., then add one tenth of the pre-emulsion solution 1 and one third of the initiator solution to initiate a polymerization reaction, then evenly drop the remaining pre-emulsion solution 1 and one third of the initiator solution, continue to react for 1 hour after the dropwise addition is completed, continue to drop the pre-emulsion solution 2 and the remaining initiator solution, and keep the temperature for reaction for 1.5 hours after the dropwise addition is completed to prepare core-shell nanoparticles;
[0008] Step 2: Preparation of core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles;
[0009] 5-10 parts by weight of acrylamide compounds, 0.5-1 parts by weight of silane compounds containing amino groups, 0.1-0.2 parts by weight of initiators and 5-10 parts by weight of bentonite are dissolved and dispersed in 100 parts by weight of deionized water, and then added to a three-necked flask containing the core-shell nanoparticles prepared in step 1, and ammonia water is added to adjust the pH of the system to 8-9. After reacting at 85° C. for 1 hour, the prepared mixture is poured into an oven for drying, and then cut and granulated to obtain core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles.
[0010] As a further solution of the present invention: the surfactant in step 1 is any one of alkylphenol polyoxyethylene ether, 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate or a combination thereof.
[0011] As a further solution of the present invention: the acrylic acid ester in the step 1 is any one of butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl methacrylate or a combination thereof.
[0012] As a further embodiment of the present invention: the polymerizable silane compound in step one is any one of 3-methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltriisopropoxysilane, or a combination thereof; the amino group-containing silane compound in step two is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminoethylaminopropyltrimethoxysilane, or a combination thereof.
[0013] As a further solution of the present invention: the initiator in step 1 and step 2 is any one of ammonium persulfate and potassium persulfate or a combination thereof.
[0014] As a further solution of the present invention: the acrylamide compound in step 2 is any one of 2-acrylamido-2-methylpropanesulfonic acid and acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide or a combination thereof.
[0015] As a further solution of the present invention: the bentonite in step 2 is any one of sodium-based bentonite and calcium-based bentonite and their modified products or a combination thereof.
[0016] As a further solution of the present invention: in the step 1, the silane polymers in the core layer of the core-shell nanoparticles can be cross-linked with each other and with the amino-containing silane compound to form a network structure.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The preparation method of the nano-particle cross-linked temperature-resistant slow-swelling particles of the present invention is simple and has low production cost. Meanwhile, the prepared nano-particle cross-linked temperature-resistant slow-swelling particles can be used as materials for improving oil recovery and have excellent market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the particle size distribution diagram of the core-shell nanoparticles prepared in Example 1.
[0020] Figure 2 This is the particle size distribution diagram of the core-shell nanoparticles prepared in Example 2.
[0021] Figure 3 This is the particle size distribution diagram of the core-shell nanoparticles prepared in Example 3. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] See also Figures 1 to 3 In an embodiment of the present invention, a method for preparing cross-linked nanoparticles with temperature-resistant slow-swelling particles is provided, and the steps of the preparation method are as follows:
[0024] Step 1: Preparation of core-shell nanoparticles;
[0025] Take 0.2-0.4 parts by weight of a surfactant, 5-10 parts by weight of an acrylate, 1-2 parts by weight of styrene and 50 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 1; take 0.5-1 parts by weight of a polymerizable silane compound and 5 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 2; take 0.1-0.2 parts by weight of an initiator and 10 parts by weight of deionized water, mix and dissolve them to obtain an initiator solution; take 0.1-0.2 parts by weight of sodium bicarbonate and 30 parts by weight of deionized water, put them in a three-necked flask, stir and dissolve them, then heat them to 85° C., then add one tenth of the pre-emulsion solution 1 and one third of the initiator solution to initiate a polymerization reaction, then evenly drop the remaining pre-emulsion solution 1 and one third of the initiator solution, continue to react for 1 hour after the dropwise addition is completed, continue to drop the pre-emulsion solution 2 and the remaining initiator solution, and keep the temperature for reaction for 1.5 hours after the dropwise addition is completed to prepare core-shell nanoparticles;
[0026] Step 2: Preparation of core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles;
[0027] 5-10 parts by weight of acrylamide compounds, 0.5-1 parts by weight of silane compounds containing amino groups, 0.1-0.2 parts by weight of initiators and 5-10 parts by weight of bentonite are dissolved and dispersed in 100 parts by weight of deionized water, and then added to a three-necked flask containing the core-shell nanoparticles prepared in step 1, and ammonia water is added to adjust the pH of the system to 8-9. After reacting at 85° C. for 1 hour, the prepared mixture is poured into an oven for drying, and then cut and granulated to obtain cross-linked temperature-resistant slow-swelling core-shell nanoparticle particles;
[0028] The surfactant in step 1 is any one of alkylphenol polyoxyethylene ether and 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate or a combination thereof;
[0029] The acrylic acid ester in step 1 is any one of butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and 2-hydroxyethyl methacrylate, or a combination thereof;
[0030] The polymerizable silane compound in step 1 is any one of 3-methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltriisopropoxysilane, or a combination thereof; the amino group-containing silane compound in step 2 is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminoethylaminopropyltrimethoxysilane, or a combination thereof;
[0031] The initiator in step 1 and step 2 is any one of ammonium persulfate and potassium persulfate or a combination thereof;
[0032] The acrylamide compound in step 2 is any one of 2-acrylamido-2-methylpropanesulfonic acid, acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide, or a combination thereof;
[0033] The bentonite in step 2 is any one of sodium-based bentonite and calcium-based bentonite and their modified products or a combination thereof;
[0034] In the step 1, the silane polymers in the core layer of the core-shell nanoparticles can be cross-linked with each other and with the amino-containing silane compound to form a network structure;
[0035] The nanoparticle cross-linked heat-resistant slow-swelling particles prepared in step 1 and step 2 are elastic and heat-resistant at 150°C;
[0036] The nano-particle cross-linked temperature-resistant and slow-swelling particles prepared in step one and step two can be used as materials for improving oil recovery.
[0037] The invention prepares a core layer by dispersing acrylate, styrene, a surfactant and an initiator in water through emulsion polymerization, then adds a polymerizable silane compound and an initiator for continued reaction to prepare nanoparticles with a shell layer of silane polymer, then adds an acrylamide compound, an amino-containing silane compound and bentonite for continued polymerization, and simultaneously the silane undergoes a cross-linking reaction, and then obtains temperature-resistant slow-swelling particles with cross-linked nanoparticles through drying and granulation.
[0038] Embodiment 1
[0039] 0.1 g of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, 0.1 g of alkylphenol polyoxyethylene ether, 2 g of methyl methacrylate, 3 g of butyl acrylate, 1 g of styrene and 50 g of deionized water were stirred and mixed to obtain a pre-emulsion solution 1; 0.5 g of vinyl triethoxysilane and 5 g of deionized water were stirred and mixed to obtain a pre-emulsion solution 2; 0.1 g of ammonium persulfate and 10 g of deionized water were mixed and dissolved to obtain a persulfate solution; Ammonium persulfate solution; 30g of deionized water and 0.1g of sodium bicarbonate are placed in a three-necked flask, stirred and dissolved, and then heated to 85°C, and then 5.6g of pre-emulsion one and 3.3g of ammonium persulfate solution are added to initiate a polymerization reaction, and then the remaining pre-emulsion one and 3.3g of ammonium persulfate solution are evenly dropped in, and after the addition is completed, the reaction is continued for 1h, and then the pre-emulsion two and 3.5g of ammonium persulfate solution are continued to be dropped. After the addition is completed, the reaction is kept warm for 1.5h to prepare core-shell nanoparticles.
[0040] 4 g of acrylamide, 1 g of 2-acrylamido-2-methylpropanesulfonic acid, 0.5 g of 3-aminopropyltriethoxysilane, 0.1 g of ammonium persulfate and 5 g of sodium bentonite were dispersed and dissolved in 100 g of deionized water, and then added to the three-necked flask containing the core-shell nanoparticles prepared in step 1, and ammonia water was added to adjust the pH of the system to 8-9. After reacting at 85 ° C for 1 hour, the prepared mixture was poured into an oven for drying, and then cut and granulated to obtain core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles.
[0041] Embodiment 2
[0042] 0.1 g of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, 0.3 g of alkylphenol polyoxyethylene ether, 5 g of methyl methacrylate, 2 g of hydroxyethyl acrylate, 3 g of butyl acrylate, 2 g of styrene and 50 g of deionized water were stirred and mixed to obtain a pre-emulsion 1; 1 g of 3-Methacryloyloxypropylmethyldimethoxysilane and 5g of deionized water are stirred and mixed to obtain a pre-emulsion 2; 0.2g of potassium persulfate and 10g of deionized water are mixed and dissolved to obtain a potassium persulfate solution; 30g of deionized water and 0.2g of sodium bicarbonate are placed in a three-necked flask, stirred and dissolved, and then heated to 85°C, and then 6.2g of pre-emulsion 1 and 3.4g of ammonium persulfate solution are added to initiate a polymerization reaction, and then the remaining pre-emulsion 1 and 3.4g of ammonium persulfate solution are evenly dropped in, and after the addition is completed, the reaction is continued for 1h, and then the pre-emulsion 2 and 3.4g of ammonium persulfate solution are continued to be dropped, and after the addition is completed, the reaction is kept warm for 1.5h to prepare core-shell nanoparticles.
[0043] Take 5g acrylamide, 3.5g N,N-dimethylacrylamide, 1.5g 2-acrylamido-2-methylpropanesulfonic acid, 0.6g 3-aminopropyltrimethoxysilane, 0.2g ammonium persulfate, 5g sodium bentonite and 5g calcium bentonite, disperse and dissolve them in 100g deionized water, then add them to the three-necked flask containing the core-shell nanoparticles prepared in step 1, add ammonia water to adjust the pH of the system to 8-9, react at 85°C for 1h, pour the prepared mixture into an oven for drying, and then cut and granulate to obtain cross-linked temperature-resistant and slow-swelling core-shell nanoparticle particles.
[0044] Embodiment 3
[0045] 0.3g of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, 2g of methyl methacrylate, 2g of hydroxypropyl acrylate, 2g of butyl acrylate, 1.5g of styrene and 50g of deionized water were stirred and mixed to obtain a pre-emulsion solution 1; 0.7g of vinyl trimethoxysilane and 5g of deionized water were stirred and mixed to obtain a pre-emulsion solution 2; 0.15g of potassium persulfate and 10g of deionized water were mixed and dissolved to obtain potassium persulfate Solution; 30g of deionized water and 0.15g of sodium bicarbonate are placed in a three-necked flask, stirred and dissolved, and then heated to 85°C, and then 5.78g of pre-emulsion one and 3.3g of ammonium persulfate solution are added to initiate a polymerization reaction, and then the remaining pre-emulsion one and 3.3g of ammonium persulfate solution are evenly dropped in, and after the addition is completed, the reaction is continued for 1h, and then the pre-emulsion two and 3.55g of ammonium persulfate solution are continued to be dropped, and after the addition is completed, the reaction is kept warm for 1.5h to prepare core-shell nanoparticles.
[0046] 5 g of acrylamide, 3 g of 2-acrylamido-2-methylpropanesulfonic acid, 1 g of 3-aminoethylaminopropyltrimethoxysilane, 0.15 g of ammonium persulfate and 7 g of calcium bentonite were dispersed and dissolved in 100 g of deionized water, and then added to the three-necked flask containing the core-shell nanoparticles prepared in step 1, and ammonia water was added to adjust the pH of the system to 8-9. After reacting at 85° C. for 1 h, the prepared mixture was poured into an oven for drying, and then cut and granulated to obtain cross-linked temperature-resistant and slow-swelling core-shell nanoparticle particles.
[0047] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles, characterized in that: The preparation method thereof has the following steps: Step 1: Preparation of core-shell nanoparticles; Take 0.2-0.4 parts by weight of a surfactant, 5-10 parts by weight of an acrylate, 1-2 parts by weight of styrene and 50 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 1; take 0.5-1 parts by weight of a polymerizable silane compound and 5 parts by weight of deionized water, stir and mix them uniformly to obtain a pre-emulsion solution 2; take 0.1-0.2 parts by weight of an initiator and 10 parts by weight of deionized water, mix and dissolve them to obtain an initiator solution; take 0.1-0.2 parts by weight of sodium bicarbonate and 30 parts by weight of deionized water, put them in a three-necked flask, stir and dissolve them, then heat them to 85° C., then add one tenth of the pre-emulsion solution 1 and one third of the initiator solution to initiate a polymerization reaction, then evenly drop the remaining pre-emulsion solution 1 and one third of the initiator solution, continue to react for 1 hour after the dropwise addition is completed, continue to drop the pre-emulsion solution 2 and the remaining initiator solution, and keep the temperature for reaction for 1.5 hours after the dropwise addition is completed to prepare core-shell nanoparticles; Step 2: Preparation of core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles; 5-10 parts by weight of acrylamide compounds, 0.5-1 parts by weight of silane compounds containing amino groups, 0.1-0.2 parts by weight of initiators and 5-10 parts by weight of bentonite are dissolved and dispersed in 100 parts by weight of deionized water, and then added to a three-necked flask containing the core-shell nanoparticles prepared in step 1, and ammonia water is added to adjust the pH of the system to 8-9. After reacting at 85° C. for 1 hour, the prepared mixture is poured into an oven for drying, and then cut and granulated to obtain core-shell nanoparticle cross-linked temperature-resistant slow-swelling particles.
2. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The surfactant in step 1 is any one of alkylphenol polyoxyethylene ether, 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, or a combination thereof.
3. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The acrylic acid ester in the step 1 is any one of butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl methacrylate or a combination thereof.
4. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The polymerizable silane compound in the step 1 is any one of 3-methacryloxypropylmethyldimethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, and vinyltriisopropoxysilane, or a combination thereof; the amino group-containing silane compound in the step 2 is any one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminoethylaminopropyltrimethoxysilane, or a combination thereof.
5. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The initiator in step 1 and step 2 is any one of ammonium persulfate and potassium persulfate or a combination thereof.
6. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The acrylamide compound in step 2 is any one of 2-acrylamido-2-methylpropanesulfonic acid and acrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide, or a combination thereof.
7. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: The bentonite in step 2 is any one of sodium-based bentonite and calcium-based bentonite and their modified products or a combination thereof.
8. The method for preparing nanoparticle cross-linked temperature-resistant slow-swelling particles according to claim 1, characterized in that: In the step 1, the silane polymers in the core layer of the core-shell nanoparticles can be cross-linked with each other and with the amino-containing silane compound to form a network structure.
9. The nanoparticle cross-linked heat-resistant and slow-swelling particles prepared by the method for preparing nanoparticle cross-linked heat-resistant and slow-swelling particles according to claim 1 are used as materials for improving oil recovery in petroleum exploitation.